Developing a water-energy-GHG emissions modeling framework: Insights from an application to California's water system. (November 2018) - Escriva-Bou, Alvar; Lund, Jay R.; Pulido-Velazquez, Manuel; Hui, Rui; Medellín-Azuara, Josué
Abstract: Integrating processes of water and energy interdependence in water systems can improve the understanding of the tradeoffs between water and energy in management and policy. This study presents a development of an integrated water resources management model that includes water-related energy use and GHG emissions. We apply the model to a simplified representation of California's water system. Accounting for water demands from cities, agriculture, environment and the energy sector, and combining a surface water management model with a simple groundwater model, the model optimizes water use across sectors during shortages from an economic perspective, calculating the associated energy use and electricity generation for each water demand. The results of California's water system show that urban end-uses account for most GHG emissions of the entire water cycle, but large water conveyance produces significant peaks over the summer season. Different policy scenarios show the significant tradeoffs between water, energy, and GHG emissions. Highlights: We develop an integrated water-energy-GHG emissions model. Water-related energy use and/or production are included for each water demand. Water allocation is modeled using a mixed simulation/optimization algorithm. 13% of electricity and 5% of GHG emissions are related with water use in California. Several scenarios show the tradeoffs between water, energy, and GHG emissions.